Keterlibatan Planner Penyandaran dan Pemberangkatan Kapal Terhadap Marketing pada Perusahaan Pelayaran PT. Nusantara Pasifik Sentosa Belawan - Yut Indah Sitohang; Suratni Ginting; Lilis Lilis (Logistics and Supply Chain Insights, 2026)
Ship berthing and departure planning is one of the crucial aspects in supporting the operational effectiveness of shipping companies. This study aims to analyze the important role of planners in ship berthing and departure activities in supporting marketing activities at PT. Nusantara Pasifik Sentosa Belawan. The method used in this research is a descriptive qualitative approach through observation and documentation study. The findings indicate that well-planned and coordinated ship berthing and departure activities provide a significant contribution to customer satisfaction, delivery punctuality, and the company’s image in the eyes of business partners. Effective planning also helps the company maintain service reliability and improve operational efficiency in port activities. However, several obstacles were identified, including lack of coordination between departments, limited information flow, and schedule disruptions caused by external factors such as weather conditions and port congestion. These challenges can affect the smoothness of operational activities and indirectly influence the company’s marketing performance. Therefore, strategies are required to improve human resource competencies, enhance digital communication systems, and strengthen cross-sector collaboration. With a well-structured planning system, PT.Nusantara Pasifik Sentosa is expected to improve its service quality and increase its competitiveness in the national shipping industry.